El Sistema de Costos y su incidencia en la Rentabilidad de la avícola “YemaSol Cía. Ltda.”, cantón Pelileo, período 2021. - Vargas Pilla, Pamela Alexandra (2023)
THE COST SYSTEM AND ITS IMPACT ON THE PROFITABILITY OF THE POULTRY COMPANY "YEMASOL CÍA. LTDA.", PELILEO CANTON, PERIOD 2021 The present research is called "The Cost System and its Impact on the Profitability of the poultry company "YemaSol Cía. Ltda.", Pelileo canton, period 2021", has been carried out to analyze the poultry company's cost system and how it affects Profitability. The poultry industry has become an influential sector within the country's economy, which is divided into two areas: egg production and chicken production. In the research, we focused on egg production and the importance of costs for the production process, using a descriptive and quantitative methodology through a non-experimental design by using techniques and instruments for data collection, such as observation, interview, and surveys that were managed by observation sheets, interview guide, and questionnaire. The results reveal that the poultry company does not manage a structured cost system that allows adequate control of raw material, labor, and indirect manufacturing costs, causing a drop in Profitability and poor management in decision-making, which allows issuing the respective conclusions and recommendations that will help to solve the difficulties that the company has. Keywords: cost system, profitability, market, poultry production.